Optimalisasi Konfigurasi Turbin Angin Untuk Peningkatan Produktivitas Energi Listrik Dalam Meningkatkan Hasil Pertanian di Kabupaten Pidie Jaya - Teuku Multazam; Fakhruddin Ahmad Nasution; Ilham Sahputra (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Food availability has an important role in the resilience and continuity of community life. The agricultural, especially in particular, potatoes, sweet potatoes, soybeans, vegetables, corn, onions, chilies and beans. Water is the main source. Realizing agricultural results, a lack of air supply will certainly have a negative impact on agricultural results that are not optimal. The dry season that hits will have an impact on air shortages, this will of course cause crop failure, making farmers lose money. Various efforts have been made to minimize these losses, one of which is by providing water pumps in their agricultural areas. Utilizing the pump requires continuous electrical energy as the main source to operate it, this will also have an impact on the costs incurred by farmers. The amount of electrical energy produced at the plant is greatly influenced by the optimal configuration factor for placing wind turbines at the location. The value of the optimal configuration is seen based on the high productivity of the electrical energy produced. This research will optimize the placement of wind turbines using 3D–5D and 5D–9D turbine configurations. Temporary research results show that the most optimal configuration is using the 5D–9D model with an energy production cost of 6,083 rupiah per year, and the daily electrical energy produced is 308.08 kilowatts.